InsurTech in the United States and Germany - What are the drivers behind the different business models? - Torsten Oletzky (Risk Management and Insurance Review, 2024)
Comparing the InsurTech ecosystems of the United States and Germany (Europe), there are significant regional differences in the choice of business models. While many InsurTechs in the United States have opted for the business model of a fully licensed insurer, this business model is much less common in Europe. In Europe, many InsurTechs seem to shy away from applying for a license as an insurer and limit themselves to the business model of a broker or a managing general agent. This paper analyzes the factors that influence an InsurTech's choice of business model when deciding whether or not to apply for an insurance license. It examines the impact of different local market environments on these decisions, as well as the role that access to venture capital plays in business model decisions and how regulators and their actions influence the decision-making process.
Keywords: 330